The Implementation of Character Education in Indonesian Language Learning for Class 3C Students at SDS IT Nurul Yaqin, East Jakarta - Sumadyo, Bambang; Susanti, Dewi Indah; Prameswari, Jatut Yoga (SCOPE: Journal of English Language Teaching, 2024)
This research aims to describe and explain that through the implementation of character education in Indonesian language learning for class 3C students at SDS IT Nurul Yaqin, East Jakarta, it can be a forum for preventing the occurrence of moral and social problems that occur in schools. The emergence of these social and moral problems giving rise to demoralization and immoral acts that occur as a result of there being no platform that supports students to channel their creativity and curiosity. This is qualitative research with descriptive methods. Interviews, observation and documentation are used as data collection techniques in this research. Research data analysis techniques This is data reduction, data presentation, and drawing conclusions. The population and sample in this study were class 3C students at SDS IT Nurul Yaqin, East Jakarta. The results of the study showed that the character values obtained from the students were religious, tolerance, discipline, work hard, independent, creative, curious, likes to read, friendly/communicative, and responsible. The implementation of character education in Indonesian language learning is seen from 3 aspects: 1). learning planning, 2). implementation of learning, 3). Learning evaluation." The implication that can be given in the research is that students will be creative in carrying out various tasks and developing their four Indonesian language skills. It is hoped that the school and parents can work together in providing space for students to develop themselves through character education by providing space. their creativity in learning.